This Christmas [compact disc] - Battistelli, Francesca (Curb/Word Entertainment, 2020)
It is the most wonderful time of the year, and who better to serenade the most special season than Grammy Award-winner, Francesca Battistelli? A childhood immersed in art, music, dance, and theatre prepared Francesca for a future of bringing all aspects of the holiday season, the sacred and the festive, to life through music. With a voice and a presence synonymous with Christmas, Battistelli is overjoyed to share her second, full-length Christmas album with the world.